Pemberdayaan Kader Lansia Melalui Kemampuan Deteksi Dini Masalah Kesehatan Fisik Dan Psikososial Pada Lansia - Eko Arik Susmiatin; Melani Kartika Sari; Linda Ishariani; Baghase Prasetyo; Cindy Maya Nuari; Dwi Nur Indah (Jurnal Pengabdian Masyarakat (Bisma), 2024)
Empowerment of elderly cadres is an important aspect in efforts to improve the welfare and quality of life of the elderly. One effective approach is through developing early detection skills for physical and psychosocial health problems This study aims to investigate ways to empower elderly cadres in this regard. Before the cadre empowerment activity in the form of education, 20 elderly cadres were measured. The results of the pre-test, which was tested for validity and reliability, showed that 85 persen dari cadre knowledge was in the poor category (with an average value of 59.5), while the education knowledge in the good category increased by 100%, with an average value of 85.83. Following the intervention, cadres' understanding of how to identify physical and mental health issues in the elderly has significantly increased. The experience of cadres and appropriate and engaging teaching strategies enhance their capacity to identify physical and mental health issues in the elderly at an early stage. To ensure that health initiatives pertaining to the welfare and quality of life of the elderly are accomplished and that cadres' ability is maintained, this activity must be sustained with support and reinforcement from all parties involved.